Outcomes of a church-based lifestyle intervention among Australian Samoans in Sydney – Le Taeao Afua diabetes prevention program. (February 2020) - Ndwiga, Dorothy W.; MacMillan, Freya; McBride, Kate A.; Thompson, Ronda; Reath, Jennifer; Alofivae-Doorbinia, Olataga; Abbott, Penelope; McCafferty, Charles; Aghajani, Marra; Rush, Elaine; Simmons, David
Abstract: Aims: To evaluate the effectiveness of a culturally adapted, church-based lifestyle intervention among Australian Samoans living in Sydney. Methods: This was a prospective, pre-post study of a church-wide education and support programme delivered by Community Coach Facilitators and Peer Support Facilitators to prevent, and promote self-management of, Type 2 diabetes. Participants completed questionnaires, anthropometric and HbA1c measurements before and 3–8 months after the intervention. The primary outcome was HbA1c. Results: Overall, 68/107(63.5%) participants completed both before and after intervention data collection (mean age 48.9 ± 14.2 years; 57.2% female). HbA1c dropped significantly between baseline and follow-up among participants with known diabetes (8.1 ± 2.4% (65 mmol/mol) vs 7.4 ± 1.8% (57 mmol/mol); p = 0.040) and non-significantly among participants with newly diagnosed diabetes (8.0 ± 2.1% (64 mmol/mol) vs 7.1 ± 2.3 (54 mmol/mol); p = 0.131). Participants with no diabetes increased their weekly moderate and vigorous physical activity (316.1 ± 291.6mins vs 562.4 ± 486.6mins; p = 0.007) and their diabetes knowledge also improved post-intervention (42.0 ± 13.5% to 61.3 ± 20.2%; p < 0.001). There were no significant reductions in blood pressure, BMI or waist circumference at follow-up. Conclusions: A structured, church-based, culturally tailored lifestyle intervention showed a number of improvements in diabetes risk among Samoans in Sydney. The intervention however, requires a more rigorous testing in a larger randomised controlled trial over a longer time period.